Ferroptosis and tumor immunotherapy: A promising combination therapy for tumors - Cai, Huazhong; Ren, Yongfei; Chen, Shuangwei; Wang, Yue; Chu, Liangmei (Frontiers in Oncology, 2023)
Low response rate and treatment resistance are frequent problems in the immunotherapy of tumors, resulting in the unsatisfactory therapeutic effects. Ferroptosis is a form of cell death characterized by the accumulation of lipid peroxides. In recent years, it has been found that ferroptosis may be related to the treatment of cancer. Various immune cells (including macrophages and CD8+ T cells) can induce ferroptosis of tumor cells, and synergistically enhance the anti-tumor immune effects. However, the mechanisms are different for each cell types. DAMP released in vitro by cancer cells undergoing ferroptosis lead to the maturation of dendritic cells, cross-induction of CD8+ T cells, IFN-γ production and M1 macrophage production. Thus, it activates the adaptability of the tumor microenvironment and forms positive feedback of the immune response. It suggests that induction of ferroptosis may contribute to reducing resistance of cancer immunotherapy and has great potential in cancer therapy. Further research into the link between ferroptosis and tumor immunotherapy may offer hope for those cancers that are difficult to treat. In this review, we focus on the role of ferroptosis in tumor immunotherapy, explore the role of ferroptosis in various immune cells, and discuss potential applications of ferroptosis in tumor immunotherapy.